Ku źródłom myśli. Gesty i transmodalność: wymiar przeżywanego doświadczenia - Claire Petitmengin (Avant, 2012)
The objective of this article is to study a deeply pre-reflective dimension of our subjective experience. This dimension is gestural and rhythmic, has precise transmodal sensorial submodalities, and seems to play an essential role in the process of emergence of all thought and understanding. In the first part of the article, using examples, we try to draw the attention of the reader to this dimension in his subjective experience. In the second part, we attempt to explain the difficulties and describe the interior process of becoming aware of it. Then we describe the structural characteristics of this dimension, and the different types of “interior gestures” which enable us to connect ourselves with it. Finally, we formulate a genetic hypothesis about the role of this dimension in cognition, on the basis of which we suggest some research paths in the neuroscientific, educational and existential domains.